2022
DOI: 10.1007/s10551-022-05099-w
|View full text |Cite
|
Sign up to set email alerts
|

Shaking Up (and Keeping Intact) the Old Boys’ Network: The Impact of the Mandatory Gender Quota on the Board of Directors in India

Abstract: Prior research on the impact of mandatory quotas in one dimension of diversity, on other dimensions, shows contradictory results. We seek to resolve this puzzle by relying on theory in social psychology on homophily and recategorization processes in hiring. In the context of a law mandating a gender quota on Indian boards, we predict and find that boards respond to the law by hiring new women directors who are similar to existing directors in terms of caste and community dimensions. We find that this homophily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 114 publications
1
11
0
Order By: Relevance
“…Our review found that while IB scholars have briefly noted this point (e.g., Sparrow & Budhwar, 1997;Thams et al, 2013;Varma et al, 2006), other scholars have given it more attention. For example, researchers have found that management teams and boards of directors of publicly listed Indian firms have high caste homogeneity (Ajit et al, 2012;Bhagavatula, Bhalla, Goel, & Vissa, 2019;Bhattacharya et al, 2022;Dayanandan et al, 2019), with one study showing that nearly 70% of Indian corporate boards had a Blau index of caste diversity of zero (Ajit et al, 2012); and that across all listed Indian firms, 90% of board positions are occupied by two caste groups (Brahmins and Vysyas) who are estimated to form about 7% of the Indian population. Research found that caste homogeneity among upper echelons has a negative effect on firm value (Bhagavatula et al, 2019;Dayanandan et al, 2019), in a way that parallels patterns that have been observed with respect to homogeneity on other demographic attributes as well (Carter et al, 2003).…”
Section: Implications Of Caste For Mnesmentioning
confidence: 99%
See 2 more Smart Citations
“…Our review found that while IB scholars have briefly noted this point (e.g., Sparrow & Budhwar, 1997;Thams et al, 2013;Varma et al, 2006), other scholars have given it more attention. For example, researchers have found that management teams and boards of directors of publicly listed Indian firms have high caste homogeneity (Ajit et al, 2012;Bhagavatula, Bhalla, Goel, & Vissa, 2019;Bhattacharya et al, 2022;Dayanandan et al, 2019), with one study showing that nearly 70% of Indian corporate boards had a Blau index of caste diversity of zero (Ajit et al, 2012); and that across all listed Indian firms, 90% of board positions are occupied by two caste groups (Brahmins and Vysyas) who are estimated to form about 7% of the Indian population. Research found that caste homogeneity among upper echelons has a negative effect on firm value (Bhagavatula et al, 2019;Dayanandan et al, 2019), in a way that parallels patterns that have been observed with respect to homogeneity on other demographic attributes as well (Carter et al, 2003).…”
Section: Implications Of Caste For Mnesmentioning
confidence: 99%
“…For example, the persistence of caste can be studied by examining the characteristics of social network processes and structures that are influenced by caste, i.e., how they are built and maintained, and whether those networks are relatively closed or open, or whether they are affective or instrumental. Studies of caste can also examine the interplay between formal and informal institutions in terms of how the latter mediate and enable resistance to changes in formal institutions, e.g., through relabeling preferences and choices as based on the norms of meritocracy (Twine, 2022) or the recategorization of individuals in light of affirmative action based on gender (e.g., recategorizing women as those from different gender to those from the same caste, Bhattacharya et al, 2022). At the same time, a caste lens can help scholars uncover additional mechanisms (e.g., cultural practices and power relations, which we touch upon below) that can help understand the persistence of informal institutions and offer explanations that might complement mechanisms that are based on social networks (Minbaeva et al, 2022).…”
Section: Caste Inequality and Informal Institutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Female participation in the upper echelons of firms has garnered a significant amount of attention from academics and policymakers over the past decade (Cumming et al , 2015; Bhattacharya et al , 2022). This study presents a systematic literature review concerning the influence of women in C-suites positions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to understand invisible inequalities because they may persist even when visible inequalities are addressed. For example, while quotas for women on Indian corporate boards has nearly tripled women directors-from 5.4% in 2013 to 15.1% in 2018-caste homogeneity remained intact, as 92% of women directors were from privileged castes (Bhattacharya, Khadka, & Mani, 2022). 1 Greater attention on invisible inequalities would not only help us to recognize and address them but also generate better understanding of inequality more broadly by documenting what might be more tacit mechanisms of inequality (e.g., cultural practices, social capital, social norms) and difficult-to-notice outcomes (e.g., workforce homogeneity, workplace exclusion).…”
mentioning
confidence: 99%